Шумелки: стихи / Борис Заходер ; худ. Э. В. Назаров - Заходер Борис Владимирович (Стихи для малышей, 2008)
Экземпляры: (201309) / Инвентарный номер: 48572 / Цена: 35.00 / Сис.шифр: Д 48572 / Авт.знак: З-38 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6